1998
DOI: 10.1111/j.1600-079x.1998.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increases gene expression for antioxidant enzymes in rat brain cortex

Abstract: During the last years several reports have demonstrated that melatonin is a efficient free radical scavenger and general antioxidant. In addition, it has been shown that this neurohormone is able to increase the activity of glutathione peroxidase in rat brain cortex as well as the gene expression for some antioxidant enzymes in the Harderian gland of female Syrian hamster. Also, it is well known that brain cells are particularly exposed to free radicals, with antioxidant enzymes as the major defense mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
189
3
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(216 citation statements)
references
References 37 publications
13
189
3
10
Order By: Relevance
“…15 Parallel to these, it was suggested that melatonin supplementation causes the antioxidant characteristic to emerge by increasing plasma zinc levels 32 and at the same time by increasing Cu-Zn-SOD activity. 33 When the part of the study related to NO was evaluated, I/R procedure did not result with significant difference in NO levels. This situation may be the result of the shortness of I/R period.…”
Section: Discussionmentioning
confidence: 95%
“…15 Parallel to these, it was suggested that melatonin supplementation causes the antioxidant characteristic to emerge by increasing plasma zinc levels 32 and at the same time by increasing Cu-Zn-SOD activity. 33 When the part of the study related to NO was evaluated, I/R procedure did not result with significant difference in NO levels. This situation may be the result of the shortness of I/R period.…”
Section: Discussionmentioning
confidence: 95%
“…Melatonin has been reported to increase tissue levels of glutathione peroxidase [66,67], an enzyme that metabolizes glutathione (an antioxidant) to its oxidized form [68] and to increase the mrna for glutathione peroxidase [69,70] in the rat brain. the possible interaction of ubiquitin in this effect of melatonin has not been directly tested.…”
Section: Melatonin/ubiquitin Interaction In Oxidative Stressmentioning
confidence: 99%
“…It has been reported that melatonin can increase the SOD and catalase activities and induces the expression and activity of GPx and GRd, regulating the redox cycle of glutathione [142][143][144][145][146][147]. The regulation of glutathione system by melatonin is also reflected by the stimulation of the rate limiting enzyme in glutathione synthesis, γ-glutamylcysteine synthase [148].…”
Section: The Antioxidant Capacity Of Melatonin and Its Actions On Mitmentioning
confidence: 99%